The Contribution of Youth and Women's Movements to the Indonesian National Awakening (1908–1945) - Rosmaida Sinaga; Adrian Maulana; Immanuel Steven Limbong; Putri Hasanah Piliang; Yosua Solafide Sinaga (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2025)
This study discusses the important role played by youth and women in the Indonesian National Awakening between 1908 and 1945. This study uses a history method. The activeness of youth and women who contributed to increasing national awareness, efforts to unite, and the development of the spirit of independence. Youth organizations such as Budi Utomo, Jong Java, and other youth organizations held the First Youth Congress and culminated in the Second Youth Congress which gave birth to the Youth Pledge. The Youth Congress succeeded in combining local identities into a united national spirit. Likewise, the women's movement led by figures such as R. A. Kartini, Dewi Sartika, and Roehana Kudus, highlighted the importance of education and liberation as a means to achieve equality and active participation in the struggle for independence. The Indonesian Women's Congress held in 1928 became a symbol of the strategic role of women in socio-political aspects. The findings of this study indicate that the struggle for Indonesian independence was not only driven by the elite class, the armed forces, but also by the strength of society from various backgrounds who had a high level of political awareness and nationalism. Therefore, youth and women are key actors in creating national identity and the direction of the nation's struggle towards independence.